2020
DOI: 10.1152/japplphysiol.00741.2019
|View full text |Cite
|
Sign up to set email alerts
|

Age has no effect on ankle proprioception when movement history is controlled

Abstract: It is generally accepted that proprioceptive ability deteriorates with age, although not all data support this view. We tested proprioception using three reliable tests at the ankle in 80 adults (19–80 yr). For all tests, the effects of muscle thixotropy were controlled. Under these conditions, we found no difference in proprioceptive acuity between young and old people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The more function-like features of the AMEDA test may underlie its sensitivity to age-related changes. Yang et al (2019) and Djajadikarta et al (2020) used the AMEDA and TTDPM to assess proprioceptive change across the life span, results showed that only the AMEDA scores showed an ankle proprioceptive decline associated with aging.…”
Section: Introductionmentioning
confidence: 99%
“…The more function-like features of the AMEDA test may underlie its sensitivity to age-related changes. Yang et al (2019) and Djajadikarta et al (2020) used the AMEDA and TTDPM to assess proprioceptive change across the life span, results showed that only the AMEDA scores showed an ankle proprioceptive decline associated with aging.…”
Section: Introductionmentioning
confidence: 99%
“…When turning the head, the arm and the steer are located outside of the field of view. Given the age-related decrease in proprioceptive acuity [16,[28][29][30],but see [31][32][33], older adults rely much more on vision than on proprioception to control movements such as bimanual upper limb movements [34], reaching or grasping [35,36] or walking [37]. The preponderance of visual inputs to maintain a stable steer control would explain why older adults exhibit more steer variability when the gaze is away.…”
Section: Discussionmentioning
confidence: 99%
“…154 Interestingly, a recent report shows that acuity of proprioception at the ankle does not diminish in healthy ageing, as tested by psychophysical methods under controlled conditions, taking into account the history of the leg muscle contractions and relaxations. 155 158 As a side note, animal studies have established that ageing results in the loss of fast-twitch motor units, but the reinnervation process in humans is not simple (see [159][160][161] ). There is hope to soon elucidate the relevant molecular pathways.…”
Section: Foot Sensitivity In the Elderlymentioning
confidence: 99%